2014
DOI: 10.1039/c4ta00289j
|View full text |Cite
|
Sign up to set email alerts
|

A work-function tunable polyelectrolyte complex (PEI:PSS) as a cathode interfacial layer for inverted organic solar cells

Abstract: Incorporation of PSS into a PEI interfacial-layer improves the inverted-OPV, and it is further enhanced by using a robust TiOx–PEI:PSS combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
(41 reference statements)
1
34
0
Order By: Relevance
“…Ampicillin is most widely used as an antibiotic for animal health (like penicillin is for human health) [14][15][16][17] because of its stability in acidic conditions. Even though, most research on optoelectronic devices demonstrated vertical (orthogonal) dipole formation; [18][19][20] the spatial orientation of the generated horizontal (or inclined) interfacial dipole in ampicillin molecule with respect to changes in pH was recently simulated by Malloci et al 21 The primary, secondary, and tertiary (cyclic amide in lactam ring) amine along with the carbonyl group (-C = O) present in ampicillin's structure provide a specific charge distribution over the molecule. 21 This resulted in an interfacial dipole with a larger magnitude (30.28 Debye) 21,22 as compared with the dipole from other amine-based molecules such as polyethyleneimine (PEI) (1.3 Debye) 23 and even penicillin (5.99 Debye).…”
mentioning
confidence: 99%
“…Ampicillin is most widely used as an antibiotic for animal health (like penicillin is for human health) [14][15][16][17] because of its stability in acidic conditions. Even though, most research on optoelectronic devices demonstrated vertical (orthogonal) dipole formation; [18][19][20] the spatial orientation of the generated horizontal (or inclined) interfacial dipole in ampicillin molecule with respect to changes in pH was recently simulated by Malloci et al 21 The primary, secondary, and tertiary (cyclic amide in lactam ring) amine along with the carbonyl group (-C = O) present in ampicillin's structure provide a specific charge distribution over the molecule. 21 This resulted in an interfacial dipole with a larger magnitude (30.28 Debye) 21,22 as compared with the dipole from other amine-based molecules such as polyethyleneimine (PEI) (1.3 Debye) 23 and even penicillin (5.99 Debye).…”
mentioning
confidence: 99%
“…1(b), the (PEI/PAA) n lm has a wide bandgap (as an insulator), which imparts an excellent carrier-blocking capability but allows limited carrier transport. [29][30][31][32] In very thin insulators (less than 3-4 nm), electrons tunnel directly through the trapezoidal potential barrier of the insulator, while in thick insulators, electrons tunnel through the triangular potential barrier under an external electric eld (Fowler-Nordheim tunneling). 33 The potential barrier formed by the energy level difference between the materials constituting the electronic device causes the accumulation of carriers at the interface, which results in band bending.…”
Section: Resultsmentioning
confidence: 99%
“…As chematic illustration of the LIL process for the fabrication of the nanogroove arrays on ITO surfaces,t he metal oxide ALD process,a nd the final device structure with interfaces between the orderly nanopatterned cathode and (3hexylthiophene): [6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) is shown in Figure 1a.D uring the preparation of the nanopatterned ITO substrate, the sample was etched chemically in bromic acid for different times (30,45,60, 75, and 90 s) to optimize the etching process and transfer the nanogroove pattern to the ITO layer. Then, the TiO 2 or ZnO ESL was deposited on the planar or nanopatterned ITO by using the ALD technique.T he complete structure of the cell is ITO/metal oxide/P3HT:PCBM/MoO 3 /Ag, as shown in Figure 1a.T he SEM image ( Figure 1b)a fter etching shows that these nanogrooves are distributed uniformly over the substrate surface.T he 3D atomic force microscopy (AFM)i mage ( Figure 1c)s hows ac lear ordered nanopattern, whichisc onsistent with the SEM images.…”
Section: Resultsmentioning
confidence: 99%
“…With advantageso fp otential low cost, light weight, and mechanicalf lexibility,o rganic solar cells (OSCs) have attracted much attention in recent years. [1][2][3][4][5][6][7][8][9] Even though the power conversion efficiency (PCE) for bulk heterojunction (BHJ) solar cells has reached more than 9%, [10][11][12] further improvements to PCE are still the main focus of intensive study.T wo strategies to improve OSC performancea re generally used, namely,t he tuning of the optical and electronic properties of the blend components [13][14][15] and the design of advanced device structures. [16][17][18][19][20][21][22] Thet uning of the optical and electronic properties of the blend components can increaset he opencircuit voltage (V oc )ofthe cell through energy-level engineering [13,14] and the short-circuit currentd ensity (J sc )t hrough bandgap engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation